2010
DOI: 10.3109/10253890.2010.499485
|View full text |Cite
|
Sign up to set email alerts
|

Maternal prenatal stress and cortisol reactivity to stressors in human infants

Abstract: Early life factors can shape the development of hypothalamic pituitary adrenal (HPA) axis. Maternal prenatal stress might constitute such an early environmental factor. As little is known about the relation between maternal prenatal stress and cortisol reactivity in human offspring, we performed a longitudinal study including four assessments of infant cortisol reactivity to stressful events in a non-clinical population. General and pregnancy-related feelings of stress and anxiety, as well as circadian cortiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(145 citation statements)
references
References 59 publications
6
130
1
8
Order By: Relevance
“…10,11 It is suggested that maternal prenatal stress is related to dysregulation of the HPA system via "fetal programing" of the offspring. [12][13][14][15] The most common and convenient method of assessing the activity of the HPA axis is measurement of salivary cortisol levels. Given the short half-life of cortisol in saliva, concentrations of salivary cortisol reveal only momentary stress.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 It is suggested that maternal prenatal stress is related to dysregulation of the HPA system via "fetal programing" of the offspring. [12][13][14][15] The most common and convenient method of assessing the activity of the HPA axis is measurement of salivary cortisol levels. Given the short half-life of cortisol in saliva, concentrations of salivary cortisol reveal only momentary stress.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have demonstrated that maternal exposure to prenatal stress can lead to permanent modification of hypothalamo-pituitary-adrenal (HPA) function and stress-related behaviors in offspring (Tollenaar et al, 2011;Whriledge & Cidlowski, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This requires investigation in early development, as the infant's HPA axis can be unpredictably active (93), allowing stress to have early impacts in the gut and gut-brain axis. It is also of note that maternal stress and anxieties prenatally also act to modulate the infant's HPA axis response (94). As to how prenatal stressors interact with maternal postnatal stress in the modulation of the infant microbiome and the composition of breast milk require further investigation, including as to the relevance of alterations in the melatonergic pathways to this.…”
Section: Breastfeeding: Modulation Of the Gut And Gut-brain Axismentioning
confidence: 99%